Review: Mangrove hybrid of Rhizophora and its parentals pecies in Indo-Malayan region - AHMAD DWI SETYAWAN; YAYA IHYA ULUMUDDIN; PANDISAMY RAGAVAN (Smujo International, 2014)
Abstract. Setyawan AD, Ulumuddin YI, Ragavan P. 2014. Mangrove hybrid of Rhizophora and its parental species in Indo-Malayan region. Nusantara Bioscience 6: 69-81. There was two putative hybrid species of mangrove in the Indo-Malayan region, namely Rhizophora x annamalayana Kathir. and R. x lamarckii Montrouz. Rhizophora x annamalayana is most recently known as a natural hybrid between R. apiculata and R. mucronata. At first, this plant is considered as R. x lamarckii, a well-known mangrove hybrid between R. apiculata and R. stylosa. Since R. stylosa is not distributed in India and Sri Lanka, the location where this species was first discovered, the name of the new hybrid species between R. apiculata and R. mucronata was corrected. Meanwhile, R. x lamarckii has long been known and is always found in habitat where its parents grew. Besides, the cross-breeding of R. mucronata and R. stylosa has never been reported. Both are sibling species that have identical morphological characteristics, thus the hybrid cross-bred species was not observed visually and can only be distinguished through genetic studies.